APLIKASI MANAJEMEN PENGOLAHAN DATA PADA PENGURUS CABANG PSSI PROVINSI D.I. YOGYAKARTA MENGGUNAKAN FRAMEWORK CODEIGNITER BERBASIS WEB - Buhari, Ahmad; Sholeh, Muhammad; Hamzah, Amir (Jurnal Jarkom, 2013)
ABSTRACT Sport is one of the factors to obtain physical healthy is directly affecting the spiritual health, as we often hear the saying